Studi iAplikasi IMy IQuran Ipada IEra IDigital IDiscruption IdiIThe IWali IStudio - Alfina Damar Yanti; Ahmad Kholid Mawardi; Ana Wahdatus Sholikhah; Dewi Safitri; Mualamatul Musawamah; Muhammad Shidqi (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2021)
Disruption iis ia ivariety iof ithings ithat irefer ito itechnology iand iis iable ito ihave ia ivery ilarge iinfluence ion ithe iindustry ior imarket. iIn ithe ipast, iwhen iAndroid ihad ia ismall iscreen, ithe iresolution iwas ilow, ithere iwas ian iAl-Quran iapplication, ibut ithe iapplication iwas ionly iin ithe iform iof icapturing iimages ifrom ithe ioriginal iAl-Quran, ithus imaking iThe iWali iStudio ithink iwith ithe iQur'an ithat iit iwas iuncomfortable. iThe iWali iStudio ias ione iof ithe idigital itechnology istartups iin ithis idisruption iera iwants ito iprovide ia isolution, inamely iby imaking ithe iMy iQuran iapplication, iwith ithe ihope ithat iThe iWali iStudio ican iprovide ia idigital iapplication imedia ithat imakes ithe ieyes icomfortable, iwhere ithe iletters ican ibe izoomed iin, ithere iis itajwid. iThere iare ivarious icolors ithat ican ibe ichosen ias idesired, ithere iare itranslations ithat ican ibe iraised iand iremoved iaccording ito ithe iwishes iof ithe iuser, iwith ia icellphone ior ilaptop, ithat's ihow ibig ithe iinfluence iof idigital idisruption iis. iThe imethod iused iin ithis istudy iis ia idescriptive iqualitative iresearch imethod iwith ia icase istudy iapproach imodel. iThis istudy iexamines icases iand iexplores ithe iMy iQuran iapplication istarting ifrom ithe idevelopment ibackground, iapplication ifeatures, ipresentation imodel, ito ithe iadvantages iand idisadvantages iof ithe iMy iQuran iapplication. iThis iresearch ialso ireveals ithat ithe ipresence iof ithe iMy iQuran iapplication ican iprovide isignificant ibenefits ifor ithe iMuslim icommunity iin iIndonesia.